The Importance of Developing Self-Control to Improve Subjective Well-Being of Adolescents Living in Orphanage - Ulfah, Khoiriya (ANFUSINA: Journal of Psychology, 2023)
Subjective well-being is a person's perception of his life experience and affection for his life Diener (1984). Based on observations, teenagers who live in orphanages seem to want more attention. Adolescents basically enter a transitional period and need guidance and affection from their parents, but they cannot get this at the orphanage. This is very risky for the emergence of negative emotions which of course will interfere with their subjective well being. So that self-control is needed to reduce negative emotions that might occur to teenagers in the orphanage. Individuals who have good self-control will be able to express their emotions appropriately according to the circumstances they are facing. This study aims to determine the relationship between self-control and subjective well-being in adolescents living in orphanages in Pringsewu Regency. The sample in this study were 60 adolescents according to predetermined criteria, namely those who resided in the orphanage of Putri Tunas Harapan Aisyiyah and Putra Umul Mukmin Aisyah Binti Abubakar in Pringsewu Regency. The data collection method in this study was to use a scale and use the Product Moment correlation technique with the help of the SPSS 20.0 for windows program using Cronbach Alpha. The results of the correlation in this study are that there is a significant positive relationship between self-control and subjective well-being.Keywords: Self-Control, Subjective Well-Being, Adolescents